Zemlia . Earth - Dovzhenko, Alexander (VUFKU, 1930)
The years of collectivization in Ukraine. Activist Vasil starts a collective farm in his village and organizes the local youth to join it. He also brings a tractor to the village which is to become the beginning of the new life. The kulaks, fearing for their possessions, kill Vasil, but his ideas and undertakings take root.